2010
DOI: 10.1016/j.ophtha.2009.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Visual Impairment and the Risk of Falls and Falls with Injury

Abstract: Objective-To evaluate central and peripheral visual impairment as independent risk factors for falls and falls with injury among adults.Design-Population-based prospective cohort study. Participants-A total of 3,203 LALES participants.Methods-Baseline presenting binocular central distance acuity was measured and impairment was classified as mild (20/40-20/63), moderate/severe (20/80 or worse). Peripheral visual impairment was classified as mild (−6dB Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 43 publications
2
82
1
2
Order By: Relevance
“…Mobility is known to be impaired with visual field loss [4] and the risk of falls is increased [3,5,28]. Given that patients with DPN also have greater likelihood of gait compromise [29] the risk of injury from falls may be further amplified by the twin mechanisms of impaired mobility control and reduced peripheral vision sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobility is known to be impaired with visual field loss [4] and the risk of falls is increased [3,5,28]. Given that patients with DPN also have greater likelihood of gait compromise [29] the risk of injury from falls may be further amplified by the twin mechanisms of impaired mobility control and reduced peripheral vision sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship could alternatively imply a common underlying neuropathological mechanism for reduction in vision and DPN-related ulceration. If this were the case, peripheral vision quality may also be compromised, and this could potentially impair mobility and balance [3][4][5]. The relationship between peripheral vision and DPN is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent prospective results from the Los Angeles Latino Eye study confirm an independent association with central and peripheral visual impairment and an increased risk of falls (OR 2.36; 95% CI 1.02-5.45 and OR 1.42; 95% CI 1.06-1.91, respectively). 47 In a study of 54 adults, aged 65 years and older with primary open angle glaucoma, participants with greater Visual loss and falls Visual loss and falls A Dhital et al binocular visual field loss had increased postural sway, both on firm and foam surfaces, independent of age, gender, body mass index, and physical performance levels. 51 Furthermore, participants with the majority of their visual field loss in the inferior field, showed increased postural sway on the foam surface.…”
Section: Glaucoma and Fallsmentioning
confidence: 97%
“…Falls frequently result from an interaction of multiple and diverse risk factors and situations, some of which are often unrecognized. Especially, poor vision has long been evocated as a risk factor for falling if undiagnosed and untreated [2,3,4,5,6]. Visual impairment occurs increasingly frequently as people age and several studies have suggested that visual impairment contributes to falls in the elderly.…”
Section: Introductionmentioning
confidence: 99%